PERJANJIAN PINJAM-MEMINJAM ANTARA BADAN DIAKONAT GEREJA DENGAN DEBITUR DI GEREJA KEMAH IBADAT AIRNONA - Mata Ratu, Dinomax; Hedewata, Agustinus; Pello, Helsina Fransiska (Petitum Law Journal, 2024)
In developing a business, a person needs capital assistance from other people who have capital and of course borrowing capital will give rise to a legal act which is based on the agreement of the parties in an agreement called a loan agreement which is commonly used in contract practice. The Airnona Tent of Worship Church itself is a church located on Jalan Kancil Number 33, Airnona Village, Kota Raja District, Kupang City. Where this church, prepares a revolving fund for micro businesses through the Church's diaconate body as program manager and runs this program with an agreement or agreement with certain conditions and in the process the returns are without interest. The main issues are as follows: (1) What is the loan and loan agreement system between the Diaconate Body as the creditor and the Congregation as the debtor at the Airnona Tabernacle Church? (2) What caused the breach of contract to occur between the parties at the Airnona Tent of Worship Church? (3) What countermeasures are used by the Diaconate body when there is a breach of contract (default) by a debtor at the Airnona Tent of Worship Church? The method used in this research is qualitative research, while using an empirical juridical approach. The data collection techniques used were interviews, observation and documentation. The aim of this research is to determine the loan agreement system used by the Church Diaconate Body with Debtors at the Airnona Tent of Worship Church. The research results show that the loan and borrowing agreement for revolving funds for micro businesses at the Tent of Worship Church has written procedures in the form of receipts, but the agreement is very simple and only includes basic information such as the name, address of the debtor, and the due date for refunding the funds without covering the rights aspect, obligations, or sanctions related to breach of agreement. The lack of effectiveness of the assessment team in analyzing data and selecting potential debtors, as well as the lack of regular supervision of each place of business, causes difficulties in dealing with debtors who experience difficulty in fulfilling payment obligations when their business conditions decline or experience bankruptcy. In dealing with problems, coping efforts are limited to verbal warnings, which are often not effective enough to overcome problems or encourage behavior change. The limited authority of Church institutions is also an obstacle, so that handling violations is limited to intensive collection efforts.